Фінансові аспекти застосування тендерних закупівель у закладах охорони здоров’я - Новожилова, К.О. (Культура народов Причерноморья, 2013)
У статті розглянено фінансові аспекти здійснення тендерних закупівель у сфері охорони
здоров’я. Особливу увагу приділено порушенням порядку проведення конкурсних торгів. Обґрунтовано
думку про те, що причини таких порушень полягають не лише в особистих інтересах замовників та
постачальників, але й у недосконалості організації закупівель в Україні, яка не враховує належним чином
специфіки діяльності медичних установ. Автор аналізує існуючі недоліки та пропонує напрямки
реформування системи тендерних закупівель.
Ключові слова: тендерні закупівлі, торги, процедура закупівлі, медичні заклади, охорона здоров’я, МОЗ,
порушення. В статье рассмотрены финансовые аспекты тендерных закупок в сфере здравоохранения.
Особое внимание уделяется нарушениям порядка проведения конкурсных торгов. Обосновывается
мысль о том, что причины таких нарушений заключаются не только в личных интересах заказчиков и
поставщиков, но и в несовершенстве организации закупок в Украине, которая не учитывает должным
образом специфику деятельности медицинских учреждений. Автор анализирует существующие
недостатки и предлагает направления реформирования системы тендерных закупок.
Ключевые слова: тендерные закупки, торги, процедура закупки, медицинские учреждения,
здравоохранение, МЗ, нарушение. The article covers financial aspects of competitive bidding at public health service in Ukraine. The
author considers the fundamentals of tender legislation and gives the statistics of tendering procedures of the
Health Department versus the whole public competitive procurement. Special attention is given to law
infringements. On the one hand, they come from the private interests of entities and suppliers. Corruption grows
up and it results in overspending of public finances and deteriorating of health care quality. On the other hand,
the organization of competitive bidding in Ukraine is not perfect and doesn’t take into account properly the peculiarities of medical establishments. Its faults outlined in the article include the preference of the lowest price
tradeoff in quality, lack of qualified specialists and ineffective training, absence of the position of a tender expert
at the manning table, etc. The author comes to conclusion that to improve procurement efficiency it’s needed to
amend the legal and regulatory framework and update related fields. There are offered the concrete ways to
enhance bidding process.
Provisions, conclusions and practical recommendations given in the article may be useful for the lecturers of
subjects “Public finance” and “Municipal Finance” which are included to the bachelor-level program in the
specialist field "Finance and Credit".
Key words: competitive bidding, tender procedure, medical establishment, public health service, Health
Department, infringement.